2011
DOI: 10.3109/15622975.2010.539270
|View full text |Cite
|
Sign up to set email alerts
|

Increased density of GAD65/67 immunoreactive neurons in the posterior subiculum and parahippocampal gyrus in treated patients with chronic schizophrenia

Abstract: The current data on GAD65/67 indicates a dysregulation of the GABAergic system in schizophrenia patients that may be associated with cognitive decline. However, a long term effect of neuroleptics on the GABAergic system cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…In addition to the decreased thalamus-FPCN coupling, we also observed abnormally increased connectivity between the thalamus and parahippocampal gyrus in patients during task performance. Structural changes in parahippocampal gyrus in patients with chronic schizophrenia have been previously reported (Schreiber et al, 2011). The current results therefore suggest that a shift from a normal thalamocortical (specifically, FPCN) coupling to an abnormal thalamolimbic coupling may contribute to WM differences between controls and patients.…”
Section: Thalamus-fpcn Disconnection In Schizophrenia During Task Persupporting
confidence: 71%
“…In addition to the decreased thalamus-FPCN coupling, we also observed abnormally increased connectivity between the thalamus and parahippocampal gyrus in patients during task performance. Structural changes in parahippocampal gyrus in patients with chronic schizophrenia have been previously reported (Schreiber et al, 2011). The current results therefore suggest that a shift from a normal thalamocortical (specifically, FPCN) coupling to an abnormal thalamolimbic coupling may contribute to WM differences between controls and patients.…”
Section: Thalamus-fpcn Disconnection In Schizophrenia During Task Persupporting
confidence: 71%
“…1 Hypofunction of the GABAergic signaling system has been hypothesized to contribute to the pathologies of schizophrenia, bipolar disorder and major depressive disorder. 2, 3, 4, 5 Multiple laboratories have demonstrated a number of dysfunctions of the GABAergic signaling system in these disorders, including: (1) altered expression of glutamic acid decarboxylase 65 and 67 kDa proteins, 6, 7, 8 the enzymes that convert glutamate to GABA; (2) microarray results that have demonstrated increased mRNA for a number of GABA(A) (GABA A ) receptor subunits in prefrontal cortex (PFC) of subjects with schizophrenia; 9, 10, 11 and (3) gene association studies that link GABA receptor subunits to schizophrenia and mood disorders. 12, 13, 14 …”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Mishra et al (2010) reported positive findings for rTMS in reducing alcohol craving. Höppner et al (2011) showed mixed findings: although rTMS had no effect on alcohol craving, the authors found that real vs. sham rTMS increased the attentional blink on alcohol-related pictures.…”
Section: Resultsmentioning
confidence: 99%